Interference effects in L-shell atomic double photoionization - Kheifets, A.; Bray, Igor; Colgan, J.; Pindzola, M. (The American Physical Society, 2011)
Angular correlation pattern in two-electron continuum is very similar in doublephotoionization (DPI) of a neutral atom ! + A ! A2+ + 2e- and electron-impact ionization ofthe corresponding singly charged ion e- + A+ ! A2+ + 2e- . This allows us to identify andinterpret interference effects in DPI of various L-shell atomic targets such as the metastableHe* 1s 2s 1S and the ground state Li 1s22s and Be 1s22s2.(Some figures in this article are in colour only in the electronic version)